Improved machine learning model selection techniques for solar energy forecasting applications - Baharin, Kyairul Azmi; Gan, Chin Kim; Zulkifly, Zaim (Gazi University, 2021)
Grid-Connected Photovoltaic System (GCPV) in Malaysia had become vital due to its usages and contribution to the community. One of the advanced technologies that has been implemented in the solar field is the forecasting of PV power output and comes with a great challenge to produce high accuracy. This paper focuses on developing a ranking system to evaluate the performance of selected machine learning models. In this paper four models are considered, namely Support Vector Machine (SVM), Gaussian Process Regression (GPR), Linear Regression, and Decision Tree. Utilizing high-resolution ground-based measurement of meteorological and PV system power output, evaluation metrics such as Root Mean Squared Error (RMSE), coefficient of determination (R2), Mean Absolute Deviation (MAD), Mean Absolute Error (MAE), and computation time has been recorded to evaluate the performance of machine learning forecasting methods. Results show that the computation time is the primary criterion that differentiates the performance of forecast models. Other statistical metrics show only marginal differences in terms of performance. The ranking system developed can serve as an indicator for solar power output forecasters to determine the best model for their application